2022
DOI: 10.3389/fendo.2022.881684
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Adipokines in the Female Reproductive System: A Focus on Polycystic Ovary Syndrome

Abstract: Adipose tissue, one type of loose connective tissue in the human body, maintains the primary task of energy storage. Adipose tissue is not only an energy reservoir but also plays a vital role as the largest endocrine organ of the whole body via releasing a variety of adipokines, which participate in many pathophysiological processes, such as energy metabolism regulation, glucose and lipid metabolism, and inflammation. Polycystic ovary syndrome (PCOS) is a disorder that mainly involves the female reproductive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 171 publications
0
15
1
Order By: Relevance
“…Considering Metrnl may play roles in insulin resistance and insulin resistance is a common finding in PCOS, two independent research teams analyzed the plasma level of Metrnl in PCOS. They both report that Metrnl level was decreased in PCOS and showed a negative correlation with insulin resistance, in contrast to changes in insulin resistance markers and FSH (54,89,90). Moreover, in studies of patients with gestational diabetes mellitus in women of a similarly child-bearing period, Metrnl levels were significantly elevated between 24 and 28 weeks of pregnancy than normal gestation (91).…”
Section: Metrnl and Polycystic Ovarian Syndromementioning
confidence: 98%
“…Considering Metrnl may play roles in insulin resistance and insulin resistance is a common finding in PCOS, two independent research teams analyzed the plasma level of Metrnl in PCOS. They both report that Metrnl level was decreased in PCOS and showed a negative correlation with insulin resistance, in contrast to changes in insulin resistance markers and FSH (54,89,90). Moreover, in studies of patients with gestational diabetes mellitus in women of a similarly child-bearing period, Metrnl levels were significantly elevated between 24 and 28 weeks of pregnancy than normal gestation (91).…”
Section: Metrnl and Polycystic Ovarian Syndromementioning
confidence: 98%
“…Leptin was also shown to directly impair the insulin-like growth factor 1 (IGF-1)-mediated augmentation of FSH-stimulated E2 synthesis by granulosa cells, suggesting that high leptin levels may contribute to infertility in some women with PCOS by counteracting the sensitizing effects of IGF-1 in dominant follicles [ 121 ]. Taken together, leptin affects the occurrence and development of PCOS by regulating the reproductive endocrine axis and ovarian steroid production, and by participating in insulin resistance [ 122 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Furthermore, this meta-analysis showed that circulating irisin was reduced in response to hyperinsulinemia in patients with PCOS, but to a greater extent than in healthy controls, suggesting that the function of patients with PCOS in this regard may be impaired. 20 Cellular behaviors and secretome profile might changes due to localized normal milieu via physiological conditions [21][22][23][24] or pathological conditions (polycystic ovarian syndrome) as in the case with irisin and vaspin. [5][6][7][8][9][10] The results of this study and the references from the previously published literature represents that both the adipocytokines were correlated with the high blood glucose level, higher BMI, and lastly, both the values remained higher in the women who had PCOS.…”
Section: Discussionmentioning
confidence: 99%